Purity, Danger, and Patriotism: The Struggle for a Veteran Home during the COVID-19 Pandemic - Ippolytos Kalofonos; Matthew McCoy (Pathogens, 2023)
The coronavirus disease 2019 (COVID-19) pandemic rendered congregate shelter settings high risk, creating vulnerability for people experiencing homelessness (PEH). This study employed participant observation and interviews over 16 months in two Veteran encampments, one located on the grounds of the West Los Angeles Veteran Affairs Medical Center (WLAVA) serving as an emergency COVID-19 mitigation measure, and the other outside the WLAVA gates protesting the lack of onsite VA housing. Study participants included Veterans and VA personnel. Data were analyzed using grounded theory, accompanied by social theories of syndemics, purity, danger, and home. The study reveals that Veterans conceptualized home not merely as physical shelter but as encompassing a sense of inclusion and belonging. They sought a Veteran-run collective with a harm reduction approach to substance use, onsite healthcare, and inclusive terms (e.g., no sobriety requirements, curfews, mandatory treatment, or limited lengths of stay). The twin encampments created distinct forms of community and care that protected Veterans from COVID-19 infection and bolstered collective survival. The study concludes that PEH constitute and belong to communities that provide substantial benefits even while amplifying certain harms. Housing interventions must consider how unhoused individuals become, or fail to become, integrate into various communities, and foster therapeutic community connections.